Acute effect of intense exercises on serum superoxide dismutase, catalase and malondialdehyde levels in soccer players - Kiyici, F.; Kishali, N. F. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The aim of this study was to investigate the changes in activity of antioxidant enzymes including superoxide dismutase (SOD) and catalase (CAT) and level of malondialdehyde (MDA) in soccer players after speed exercise. METHODS: This study was carried out on 18 soccer players who do regular sports activities and are healthy. Blood samples were taken before and after exercises at the beginning and end of 10 consecutive training programs for SOD and CAT activities and MDA level. RESULTS:The mean SOD levels were 1.74 and 2.50 U/mL and the mean CAT levels were 0.16 and 5.26 U/mL before and after exercise at the beginning of the training program (PCONCLUSION: In conclusion, acute exercise resulted in ROS production, and consequently worsened lipid peroxidation as reflected by increased MDA level, possibly through exhausting the antioxidant defence system.